B-Lynch Transverse Compression Suture for PPH Placenta Previa Bleeding - B-Lynch, C; Meyer, K K; Javaid, T A (Nepal Journal of Obstetrics and Gynaecology, 2014)
Postpartum hemorrhage (PPH) is a serious condition. Fourteen million cases of PPH occur worldwide each year. DOI:http://dx.doi.org/10.3126/njog.v9i2.11723